Encapsulation of an ionic liquid into the nanopores of a 3D covalent organic framework. Issue 3 (5th January 2017) - Xin, Yingxiang; Wang, Chang; Wang, Yu; Sun, Jianjun; Gao, Yanan
Abstract : An ionic liquid [Emim][Tf2 N] confined into the nanopores of three-dimensional COF-320 demonstrated an increased melting point. Abstract : An ionic liquid was confined inside the nanopores of a three-dimensional (3D) COF for the first time. The confined ionic liquid was remarkably solidified due to the nanosized effect of the COF on the ionic liquid. This research provides a novel strategy for immobilizing ionic liquids on solid supports or within a solid matrix.